Co-incidence of COVID-19 and hepatocellular carcinoma during pregnancy: Double punches to disease severity and mortality? - Abubakar, Azzaki; Yusuf, Fauzi; Firdausa, Sarah; Maghfirah, Desi; Gunawan , Andrie; Sari, Fitrah (Narra J, 2023)
Hepatocellular carcinoma (HCC), a considerable leading cause of cancer-related deaths worldwide, is the most common primary liver cancer with poor prognosis and outcome. Many advances in prevention, screening, and new technologies in diagnostics and therapy have been achieved, but its incidence and mortality remain increasing. Co-infection of another viral disease in HCC patients with pregnancy might exacerbate the condition and double the mortality rate. The aim of this case report was to describe the co-infection of coronavirus disease 2019 (COVID-19) in an HCC patient during pregnancy. A 26-year-old woman with 16–17weeks of gestation was admitted to Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia with shortness of breath. The patient also reported that the abdomen expanded rapidly in the last three weeks, followed by severe pain and collateral vein appearance. Laboratory findings revealed anemia, leukocytosis, HBsAg reactive, hypoalbuminemia, hyperbilirubinemia, elevated liver enzymes, increased alpha-fetoprotein (AFP), and cancer antigen 125 (CA-125). Ultrasonography indicated gestation with a single fetus, an enlarged liver with a 9.9 x 9.4 cm nodule, and massive ascites. The patient was also RT-PCR-confirmed COVID-19. On day 8 of hospitalization, the patient suddenly reported severe abdominal pain. Ultrasonography revealed fetal distress immediately followed by fetal death. Adequate management of cancer pain, continuous evacuation of ascites, and other supportive care could not save the patient who died on the day 17 of hospitalization. In this case, we found no proof that the patient experienced cirrhosis prior to HCC. Pregnancy through hormonal alteration is thought to be the aggravating factor that accelerates the progression of pre-existing liver disease into carcinoma and infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) worsened the outcome in this patient.